Characteristics of IL-9 induced by Schistosoma japonicum infection in C57BL/6 mouse liver - Lu Li; Hongyan Xie; Mei Wang; Jiale Qu; Hefei Cha; Quan Yang; Yuanfa Feng; Yanwei Qi; Huaina Qiu; Nuo Dong; Jun Huang (Scientific Reports, 2017)
Abstract Liver granulomatous inflammation and fibrosis were the primary pathological changes observed during Schistosoma japonicum (S. japonicum) infection. In the present study, the characteristics of IL-9 were investigated in the liver of S. japonicum infection C57BL/6 mice. Immunofluorescence, qRT-PCR, and ELISA results demonstrated that the expression of IL-9 significantly increased after infection (P < 0.01). FACS results indicated that the peak of IL-9+ Th9 cells in the liver mononuclear cells appeared at the early phase of infection (week 5), except that Th9 cells, CD8+ Tc cells, NKT and γδT cells could secrete IL-9 in this model. Although IL-9 neutralization has a limited effect on liver granulomatous inflammation, it could decrease the level of fibrosis-associated factor, PC-III, in the serum of infected mice (P < 0.05). Taken together, our results indicated that IL-9 was an important type of cytokine involved in the progression of S. japonicum infection-induced hepatic damage.